2022
DOI: 10.3389/fonc.2022.1079446
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics profiles refine L-dopa decarboxylase (DDC) as a reliable biomarker for prognosis and immune microenvironment of clear cell renal cell carcinoma

Abstract: BackgroundIncreasing evidence indicates that L-dopa decarboxylase (DDC), which mediates aberrant amino acid metabolism, is significantly associated with tumor progression. However, the impacts of DDC are not elucidated clearly in clear cell renal cell carcinoma (ccRCC). This study aimed to evaluate DDC prognostic value and potential mechanisms for ccRCC patients.MethodsTranscriptomic and proteomic expressions of and clinical data including 532 patients with ccRCC (The Cancer Genome Atlas RNA-seq data), 226 ccR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…A recent study reported that upregulated IL20RB is confirmed as a novel prognostic and therapeutic biomarker in KIRC, which is consistent with our results 28 . It was also reported that downregulated DDC is significantly associated with poor survival and an immune‐suppressive TME in KIRC 29 . Another study confirmed that decreased TEK expression had a poor prognosis for patients with KIRC 30 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent study reported that upregulated IL20RB is confirmed as a novel prognostic and therapeutic biomarker in KIRC, which is consistent with our results 28 . It was also reported that downregulated DDC is significantly associated with poor survival and an immune‐suppressive TME in KIRC 29 . Another study confirmed that decreased TEK expression had a poor prognosis for patients with KIRC 30 .…”
Section: Discussionsupporting
confidence: 91%
“…28 It was also reported that downregulated DDC is significantly associated with poor survival and an immune-suppressive TME in KIRC. 29 Another study confirmed that decreased TEK expression had a poor prognosis for patients with KIRC. 30 We evaluated their prognostic value using a risk score and found that the low-risk group had a significantly better prognosis than the high-risk group.…”
Section: Discussionmentioning
confidence: 91%